Make America Hate Again: Donald Trump and the Birther Conspiracy - Stephanie Kelley-Romano; Kathryn L. Carew (Journal of Hate Studies, 2019)
One of the most publicized and commonly embraced political conspiracies has been the birther movement. The conspiracy, which gained traction amid the 2008 Presidential election, alleged that Barack Obama was ineligible for the Presidency on grounds he was not born in the United States. Though the movement was continuously debunked by a myriad of people, birthers remarkably managed to keep the conspiracy alive and relevant, due in large part to Donald Trump. Analysis of birther rhetoric, and specifically Donald Trumps use of it to continually undermine Barack Obama, provides a particularly robust understanding of the rhetorical forms that facilitate the resiliency of conspiracy. In this essay, we combine Richard Hofstadters concept of the paranoid style with generic approaches to conspiracy to unpack the ways birther rhetoric functionsboth formally and stylisticallyto advance a rhetoric of white supremacy. Furthermore, we analyze Donald Trumps role as conspiracy advocate and the specific rhetorical strategies he employs to use the birther controversy for his political advantage. Keywords: Barack Obama, birther movement, white supremacy, hate speech